Central obesity may account for most of the colorectal cancer risk linked to obesity: evidence from the UK Biobank prospective cohort - Safizadeh, Fatemeh; Mandić, Marko; Schöttker, Ben; Hoffmeister, Michael; Brenner, Hermann (International journal of obesity, 2025)
General obesity commonly represented by body mass index (BMI) is an established risk factor for colorectal cancer (CRC). However, it is unclear to what extent this association is accounted for by central obesity. We aimed to evaluate the associations between BMI, waist-to-hip ratio (WHR), and waist circumference (WC) with CRC risk and to investigate if and to what extent these associations are independent from each other.
Online verfügbar: 19. November 2024
Gesehen am 14.05.2025